Public housing renewal and social determinants of health. Issue 4 (1st October 2016) - Arthurson, Kathy; Levin, Iris; Ziersch, Anna
ABSTRACT: This article draws on the concept of residential context of housing and its relationship to health. It considers a bundle of changes through implementation of a housing renewal initiative as part of the Carlton Housing Estate Upgrading Project in Melbourne, Australia. Beyond the quality and appropriateness of the housing, pertinent factors explored include social networks, safety and security, and green open space. Data collection for the research project included in-depth interviews with public housing tenants, private residents, and service providers who live on and service the estate, as well as neighborhood observations and participation in on-site events. A key finding was that the relational processes of how tenants were related to by others–specifically, the way housing was reallocated during the processes of renewal–affected social housing tenants' self-perceived health and well-being.